Chicago sky blue gel for better visualization of Demodex in patients with Demodex blepharitis - Lunla Udomwech; Weeratian Tawanwongsri; Auemphon Mordmuang (PeerJ, 2023)
Background Demodex blepharitis is a common chronic disease. The number of mites is associated with ocular discomfort. The accurate number derived from well-stained specimens is, hence, in favor of diagnosing, monitoring, and determining treatment responses. Methods A cross-sectional study was conducted between April and July 2022 at the dermatology and ophthalmology clinic, Walailak University, Thailand. Adult participants with clinical suspicion of Demodex blepharitis were recruited. We examined eyelashes under light microscopy to quantify the number of Demodex mites before and after adding CSB gel. The mite counts, evaluated by an untrained investigator and an experienced investigator, were recorded and compared. Results A total of 30 participants were included for final analysis, among which 25 (83.3%) were female. The median age was 64.0 years (IQR, 61.0–68.0). The median Demodex counts evaluated by the experienced investigator before and after adding CSB gel were 1.0 (IQR, 0.0–1.0) and 2.5 (IQR, 2.0–3.0), respectively (p < 0.001). Moreover, the median Demodex counts evaluated by the untrained investigator before and after adding CSB gel were 1.0 (IQR, 0.0–1.0) and 2.0 (IQR, 1.0–3.0), respectively (p < 0.001). The correlation coefficient between Demodex counts after the addition of CSB counted by the experienced investigator and those counted by the untrained investigator was 0.92 (p < 0.001). CSB gel is a promising product to identify and quantify the number of Demodex mites. The findings supported the consideration of CSB gel as one of the diagnostic stains.